An Iberian Heritage: Hispano-Moresque architectural tiles in Portuguese and Spanish collections - Coentro, Susana Xavier (2017)
This is the first archaeometric study comparing Hispano-Moresque tiles from different Portuguese and Spanish collections, no other published one being known at the time of writing. Despite the increasing interest in the Iberian ceramic cultural heritage, a specific study dedicated to architectural tiles was lacking. With this in mind, this thesis offers a first approach on the technological features of these impressive – although somehow undervalued – architectural tiles. With this work, important Portuguese and Spanish Hispano-Moresque tile collections are characterised, compared and studied: National Palace of Sintra (Portugal) (PNS), Monastery of Santa Clara-a-Velha (Coimbra, Portugal) (SCV), archaeological site of Santo António da Charneca (Barreiro, Portugal) (SAC), Instituto Valencia de Don Juan (Madrid, Spain) (IVDJ), Casa de Pilatos (Seville, Spain) (CPS) and Museo de Cerámica y Artes Sumtuarias “González Marti” (Valencia, Spain) (MCV). The aim is to provide a physicochemical characterisation of both the glazes and the ceramic bodies of the tiles to better understand the production technology. The methodology proposed for this study had the main purpose of developing a minimally invasive and essentially non-destructive approach with complementary analytical techniques that will allow for replication in future studies with other Hispano-Moresque tile collections. The techniques chosen were: Micro-Particle Induced X-Ray Emission (μ-PIXE), Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS), Scanning Electron Microscopy with X-ray Microanalysis (SEM-EDS), μ-Raman spectroscopy, Micro-X-ray diffraction (μ-XRD) and Synchrotron Radiation Micro-X-ray diffraction (SR-μ-XRD). The archaeometric study concluded that calcareous clays were the standard material used for the ceramic bodies of the tiles. Lime content is frequently higher than 20 wt.%, which is a high value among the typical calcareous clays analysed in the literature, although within the expected results for tinopacified ceramic bodies. The glaze technology employed in Hispano-Moresque tiles followed the Islamic tradition that was introduced in the Iberian Peninsula from the 8th century onwards. High-lead glazes (ca. 30-50 wt.% PbO) were identified in all analysed samples. Two types of high-lead glazes were identified: “transparent” and tin-opacified. Besides the disparity in tin contents, the two glaze types also evidence differences in sodium and lead values. A sodium compound (most likely NaCl) may have been added to compensate the lower PbO content in tin-opacified glazes. The pictorial layer is composed of five colours: white (SnO2), blue (SnO2 + CoO), green (CuO), amber (Fe2O3) and brown (MnO). These colours exhibit different shades depending on the glaze recipe, its thickness and the influence of the underlying ceramic body. White and blue are consistently tin-opacified, whereas most green, amber and brown glazes are transparent. The results of the archaeometric study identify a widespread ceramic technology. Nevertheless, it is still visible a higher proximity between the CPS, IVDJ-Seville, SCV and PNS collections – although with differences among them – whereas the MCV and IVDJ-Toledo groups display distinct features that attest for their different provenance.